E-KATALOG: Langkah Strategis Pemerintah dalam Memerangi Fraud Pengadaan Barang dan Jasa - Ariza, Dani (Perhimpunan Sarjana Ekonomi dan Bisnis, 2024)
This research aims to investigate the effectiveness of e-catalogs as a strategic government initiative in combating fraud in the procurement of goods and services. E-catalogs represent an innovation in the procurement process expected to enhance transparency, speed, and reliability in the selection of suppliers by the government. The research employs a juridical normative approach, detailing references from books, regulations, and relevant literature. The findings of the research indicate that the use of e-catalogs has had a positive impact on clarity, process acceleration, and ease in selecting suppliers. However, the study also identifies potential security loopholes that need attention to enhance resilience against fraud within the system. While e-catalogs enable open access to prices, the research highlights the need for additional strategies to address the potential for high price negotiations. The implications of these findings can serve as a foundation for the government to continually develop and improve the security of e-catalogs as an effective tool in maintaining integrity and transparency in the procurement of goods and services.